2015
DOI: 10.1039/c5nj02080h
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar-structured biomass-derived phosphorus- and nitrogen-co-doped porous carbon for high-performance supercapacitors

Abstract: Carbon derived from fish scale, prepared through chemical activation, exhibits excellent supercapacitive performance in aqueous and ionic liquid electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…Hence, the high levels of pyrrolic‐N and graphitic‐N on BHPC‐700 would be beneficial for contributing pseudocapacity and improving conductivity for energy storage. Although the P and S contents on the BHPC‐700 are relatively low, the P doping could stabilize oxygen functionalities on the BHPC‐700 during the electrochemical charging, and consequently improve the reaction stability . Moreover, the S atoms offer reversible pseudo‐sites and a more polarized surface for BHPC‐700, which would result in superior capacitive performance …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the high levels of pyrrolic‐N and graphitic‐N on BHPC‐700 would be beneficial for contributing pseudocapacity and improving conductivity for energy storage. Although the P and S contents on the BHPC‐700 are relatively low, the P doping could stabilize oxygen functionalities on the BHPC‐700 during the electrochemical charging, and consequently improve the reaction stability . Moreover, the S atoms offer reversible pseudo‐sites and a more polarized surface for BHPC‐700, which would result in superior capacitive performance …”
Section: Resultsmentioning
confidence: 99%
“…Although the P and S contents on the BHPC-700 are relatively low, the P doping could stabilize oxygen functionalities on the BHPC-700 during the electrochemical charging, and consequently improve the reaction stability. 29 Moreover, the S atoms offer reversible pseudosites and a more polarized surface for BHPC-700, which would result in superior capacitive performance. 30 According to N 2 adsorption-desorption isotherms, SEM images, and XPS analysis, it can be deduced that the BHPC-700 sample possessed not only a large SSA and welldeveloped porosity but also abundant heteroatom functionalities.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Because N doping can enhance the electronic conductivity and wettability, while O, B, S or P-doping can provide the pseudo-capacitance, enlarge the carbon interlayer distance and increase additional active sites, N, O co-doping [34,122,123,129,138], N, B co-doping [35,147], N, S codoping [81,92,146,148] and N, P co-doping [39,99,149] have been designed to further improve the electrochemical performances of biomass-derived carbon materials. For instance, Sun et al [147] reported a separated N, B co-doped porous graphitic carbon from nitrogencontaining chitosan through coordinating boric acid and Fe catalyst, and followed by ZnCl 2 -activation process.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…In addition, the biomass-derived carbon materials with 2D sheets have been prepared by carbonized leaf [34,[90][91][92], stalk [25,93], nutshell [94], waste coffee grounds [95], okara [96], eggplant [97], silk [98], fish scale [99], biomass-based molecules (chitosan [100] and gelatin [35]), etc. These biomass precursors themselves have a multiple layer structure or cause a new structural rearrangement to form 2D sheets during the pyrolysis.…”
Section: Tubular Structurementioning
confidence: 99%
“…Various precursors with different heteroelement species [15][16][17][18] or increased amount of heteroatoms [4,9,10,[19][20][21][22] including N [20,[23][24][25], P [4,[15][16][17][18][26][27][28][29][30], S [31][32][33][34], Si [9,21,22], and Sn-doping [7,35,36] have been explored to upgrade the carbonaceous anodic materials for Li + ion storage due to their great high theoretical specific capacity of Li + ion storage. Although boron could effectively adjust the lattice defect related to the structure disorder of carbon materials, there are quite few reports on boron-doped carbon as Li + ion storage anode [37].…”
Section: Introductionmentioning
confidence: 99%